Impact of the National Early Warning Score-based sepsis response system on hospital-onset sepsis in a tertiary hospital in South Korea - Dong-gon Hyun; Sohyeon Lee; Sunhui Choi; Jeongsuk Son; So-Hee Park; Sang-Bum Hong; Chae-Man Lim (Acute and Critical Care)
Background The effectiveness of electronic medical record-based alert systems, response protocols for sepsis diagnosis, and treatment in hospitalized patients remains unclear. This study aimed to determine whether the introduction of an electronic medical record-based sepsis response protocol (SRP) along with a 24/7 operating rapid response system affects the prognosis for patients with hospital-onset sepsis. Methods In August 2022, an SRP based on the National Early Warning Score was implemented in the electronic medical record system at Asan Medical Center. We retrospectively analyzed patients screened by the detection system for 1 year after the SRP implementation. Patients of the first 6 months (preliminary group) and those of the second 6 months (SRP group) were matched 1:1 based on propensity scores. The primary outcome was 30-day mortality. Results Of the 608 hospitalized patients screened by the system, 176 were assigned to each group after 1:1 propensity score matching. Patients in the SRP group were significantly more likely to receive blood cultures (58.5%) compared with the preliminary group (45.5%) (P=0.019). The SRP group showed a lower 30-day mortality risk (hazard ratio, 0.56; 95% CI, 0.36–0.86; P=0.017) compared to the preliminary group. A restricted cubic spline curve showed that SRP survival benefit began to manifest after the first 4 months (P=0.036). Conclusions Alongside an existing rapid response system, the National Early Warning Score-based SRP in the electronic medical record reduced mortality for hospital-onset sepsis within 1 year.